Genome‐wide identification of a competing endogenous RNA network in cholangiocarcinoma. Issue 11 (3rd July 2019) - Li, Ganxun; Liu, Tongtong; Zhang, Bixiang; Chen, Weixun; Ding, Zeyang
Abstract: Cholangiocarcinoma (CCA) is the second widespread liver tumor with relatively poor survival. Increasing evidence in recent studies showed long noncoding RNAs (lncRNAs) exert a crucial impact on the development and progression of CCA based on the mechanism of competing endogenous RNAs (ceRNAs). However, functional roles and regulatory mechanisms of lncRNA‐regulated ceRNA in CCA, are only partially understood. The expression profile of messenger RNAs (mRNAs), lncRNAs, and microRNAs (miRNAs) downloaded from The Cancer Genome Atlas were comprehensively investigated. Differential expression of these three types of RNA between CCA and corresponding precancerous tissues were screened out for further analysis. On the basis of interactive information generated from miRDB, miRTarBase, TargetScan, and miRcode public databases, we then constructed an mRNA‐miRNA‐lncRNA regulatory network. Kyoto Encyclopedia of Genes and Genomes and Gene Ontology analyses were conducted to identify the biological function of the ceRNA network involved in CCA. As a result, 2883 mRNAs, 136 miRNAs, and 993 lncRNAs were screened out as differentially expressed RNAs in CCA. In addition, a ceRNA network in CCA was constructed, composing of 50 up and 27 downregulated lncRNAs, 14 up and 7 downregulated miRNAs, 29 up and 25 downregulated mRNAs. Finally, gene set enrichment and pathway analysis indicated our CCA‐specific ceRNA network was related with cancer‐related pathway and molecular function. In conclusion, our research identified a novel lncRNA‐related ceRNA network in CCA, which might act as a potential therapeutic target for patients with CCA. Abstract : In this work, our research identified the novel long noncoding RNA‐related competing endogenous RNA network in cholangiocarcinoma (CCA), which could serve as a potential therapeutic target for patients with CCA.